PARTICIPATION OF UKRAINE IN AN INTERNATIONAL SYSTEM OF TAXATION AND FINANCIAL INFORMATION EXCHANGE (IN ACCORDANCE WITH CRS STANDARDS) IN THE CONTEXT OF CRIMINAL RESPONSIBILITY FOR THE AVOIDANCE OF TAX PAYMENTS IN UKRAINE - Бахмач, Андрій Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: system of automatic exchange of financial information (AEOI) was established in 2014 as a universal mechanism of financial information exchange between the countries, participants in abovementioned system. The process of becoming a member of AEOI gives the taxation organizations of the countries-participants of the system an opportunity to obtain financial information about their tax residents, who are accountable for having bank accounts abroad. As a result of abovementioned system, the falsification and hiding of real income of the citizens abroad becomes impossible, thus it becomes easier for the country to trace the evidence of tax payment avoidance. The aim of the work is to research the process of automatic taxation and financial information exchange system establishment in Ukraine (in accordance with CRS standards). Research methods: methods used in this research goes as following: comparative-law analysis, systematic analysis, cognitive-analytical, data base analysis etc. Results: author arrives at the conclusion that the dates of establishment of the automatic taxation and financial information exchange system in Ukraine (in accordance with CRS standards) in Ukraine are not being followed sufficiently. Discussion: in this paper author discusses the importance of systematic and methodological establishment of the automatic taxation and financial information exchange system in Ukraine (in accordance with CRS standards) as well as suggests the methods that would efficiently speed up the process of law enforcement project development in Ukraine as well as other normative-law acts.